ANALYSIS OF FACTOR AFFECTING INFANT MORTALITY RATE (IMR) IN EAST JAVA USING MULTIPLE LINEAR REGRESSION - Weike Retno Palupi; Lailatul Khusnul Rizki (Universitas Airlangga, 2020)
Infant Mortality Rate (IMR) is one of the important indicators in public health. Indonesia still has a relatively high IMR compared to the neighboring countries. Based on the Indonesian Demographic Health Survey (IDHS) in 2012, IMR in East Java reached 25.50 deaths per 1000 births. IMR decline occurred during 2012 to 2015. Achievement depends on the factors that influence it. This study aims to create a model of IMR based on maternal and external factors in East Java. The method used was a non-reactive study using 38 districts/cities as sample units in East Java, which came from Central Bureau of Statistics secondary data in 2015. Statistical analysis used multiple linear regression. The results showed the independent variables together affected the IMR (p-value = 0,000 <0.05), but partially influenced by the age of the first married mother (p-value = 0,000 <0.05) and the helper delivery of non-medical personnel (p-value = 0.014 <0.05). The conclusion of this study is the regression equation model for IMR in East Java in 2015, which is IMR = 1,064 + 1,319 * (age of first marriage) + 0.439 * (helper of non-medical births). Suggestions for the Government of East Java Province to implement strategies so that infant mortality cases can be reduced.